+0  
 
0
92
1
avatar

Hello, i've posted this yesterday but I haven't gotten it answered yet:(

 Dec 4, 2019
 #1
avatar+109064 
+1

8 -3x - 1 *  (1/16)x  =  42x

 

We can write eveything in terms  of base  2....so we have

 

(2^3)^(-3x - 1) *  (1/ 2^4)^x =  (2^2)^(2x)       simplify

 

(2) ^(-9x - 3) * ( 2^-4)^x  = (2)^(4x)

 

(2)^(-9x - 3) * (2)^(-4x)  = (2)^(4x)

 

Using the property that    a^m * a^n  = a^(m + n)     we have

 

(2)^(-9x - 3 - 4x)  =  2^(4x)      the bases are the same.....olve for the exponents

 

-9x - 3 - 4x  =  4x

 

-13x - 3  = 4x      add 13x to both sides

 

-3  = 17x       divide both sides by 17

 

x = -3 / 17

 

 

cool cool cool

 Dec 4, 2019

18 Online Users

avatar